Exploring gut microbiota’s role in rheumatic valve disease: insights from a Mendelian randomization study and mediation analysis - Chen, Xiwei; Hu, Guangwen; Ning, Dong; Wang, Daxin (Frontiers in Immunology, 2024)
Background: Investigating the relationship between gut microbiota and Rheumatic Valve Disease (RVD) is crucial for understanding the disease's etiology and developing effective interventions. Our study adopts a novel approach to examine the potential causal connections between these factors.Methods: Utilizing a two-sample Mendelian Randomization (MR) framework, we incorporated a multi-variable MR (MVMR) strategy to assess the mediatory mechanisms involved. This approach involved analyzing data from the MiBioGen consortium for gut microbiota and the FinnGen for RVD, among other sources. Instrumental variables (IVs) were carefully selected based on rigorous MR principles, and statistical analysis was conducted using bidirectional two-sample MR, such as inverse variance-weighted (IVW), weighted median, MR-Egger regression and MR Steiger Test methods. The MR-PRESSO strategy was employed for outlier detection, and MVMR was used to untangle the complex relationships between multiple microbiota and RVD.Results: Our analysis highlighted several gut microbiota classes and families with potential protective effects against RVD, including Lentisphaerae, Alphaproteobacteria, and Streptococcaceae. In contrast, certain genera, such as Eubacterium eligens and Odoribacter, were identified as potential risk factors. The MVMR analysis revealed significant mediation effects of various immune cell traits and biomarkers, such as CD4 -CD8 -T cells, CD3 on Terminally Differentiated CD8+ T cell and Pentraxin-related protein PTX, elucidating the complex pathways linking gut microbiota to RVD.This study underscores the intricate and potentially causal relationship between gut microbiota and RVD, mediated through a range of immune and hormonal factors. The use of MVMR in our methodological approach provides a more comprehensive understanding of these interactions, highlighting the gut microbiota's potential as therapeutic targets in RVD management. Our findings pave the way for further research to explore these complex relationships and develop targeted interventions for RVD.